FUSION CONCEPT BETWEEN CONTEMPORARY MEDICINE AND NATURAL PRODUCTS: A NEW PARADIGM IN THE DESIGN OF SAFER MEDICINE - Mohamed, Farahidah; Harun @ Ismail, Ahmad Fahmi; Mohd Shafri, Mohd Affendi (2017)
Drug-drug combinations in a single dosage form have become a routine approach to get synergistic effect and improved compliance. However, such combinations usually do not reduce overall side-effects or adverse effects. Here, we attempted fusion between contemporary and natural products aiming to see synergistic effects and reduction in the toxicity. Drug of choice was gentamicin whereas the natural product was Nigella sativa oil formulated into microspheres dosage form. Promising results were demonstrated from the in vitro and in vivo testing suggesting potential application in clinical setting.